2015
DOI: 10.1088/0256-307x/32/9/090601
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation and Frequency Measurement of the Strontium Optical Lattice Clock at NIM

Abstract: An optical lattice clock based on 87 Sr is built at National Institute of Metrology (NIM) of China. The systematic frequency shifts of the clock are evaluated with a total uncertainty of 2.3×10 −16 . To measure its absolute frequency with respect to NIM's cesium fountain clock NIM5, the frequency of a flywheel H-maser of NIM5 is transferred to the Sr laboratory through a 50-km-long fiber. A fiber optical frequency comb, phase-locked to the reference frequency of this H-maser, is used for the optical frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 30 publications
1
53
0
2
Order By: Relevance
“…*ssr+ah*sah+rb*srb+sensm 120))+dmu*(x-58305)/365.225)+sensq 0))+dq*(x-58305)/365.225)+sensalph* 120))+dalph*(xA summary of this work, as well as six other Yb absolute frequency measurements (yellow)[18,[27][28][29][30][31], and seventeen Sr measurements (red)[9,10,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].Sr measurements are multiplied by the Yb/Sr ratio and the error bars are expanded as descibed in the main text. The fit function (orange) constrains possible variation of the Yb/Cs ratio, and the shaded region represents the 1σ uncertainty of the fit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…*ssr+ah*sah+rb*srb+sensm 120))+dmu*(x-58305)/365.225)+sensq 0))+dq*(x-58305)/365.225)+sensalph* 120))+dalph*(xA summary of this work, as well as six other Yb absolute frequency measurements (yellow)[18,[27][28][29][30][31], and seventeen Sr measurements (red)[9,10,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].Sr measurements are multiplied by the Yb/Sr ratio and the error bars are expanded as descibed in the main text. The fit function (orange) constrains possible variation of the Yb/Cs ratio, and the shaded region represents the 1σ uncertainty of the fit.…”
mentioning
confidence: 99%
“…measurements[18,[27][28][29][30][31], ν avg Yb = 518 295 836 590 863.714(98) Hz. For the Sr frequency, we likewise determine a weighted average of 17 previous measurements[9,10,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], ν avg Sr = 429 228 004 229 873.055(58) Hz. The frequency ratio derived from absolute frequency measurements is therefore, R avg abs = ν avg Yb /ν avg Sr = 1.207 507 039 343 337 86…”
mentioning
confidence: 99%
“…The instability of the TOC is dominated by the performance of the interrogation laser [45] through the Dick effect [50]. It is lower than achieved in typical single ion clocks [3,12,31,51], and comparable to many high performance lattice clocks [2,32,[52][53][54][55][56].…”
Section: Selected For a Viewpoint In Physics P H Y S I C A L R E V I mentioning
confidence: 99%
“…As well as the five direct optical frequency ratio measurements already discussed, these included 16 new absolute frequency measurements: one each of the 1S-2S transition in 1 H [18], the optical clock transitions in 171 Yb [19] and 88 Sr + [20] and the ground state hyperfine transition in 87 Rb [21], two each of the E2 [9,14] and E3 [9,15] transitions in 171 Yb + and the reference transition in 40 Ca + [22], and six of the optical clock transition in 87 Sr [23,24,25,26,27,28]. In addition, a correction [29] was submitted to a previously-used absolute frquency measurement of the optical clock transition in 199 Hg [30] and one earlier absolute frequency measurement of the reference transition in 40 Ca + [31] was withdrawn as new data from the same group suggested that the systematic frequency shifts may have been underestimated in this measurement [22].…”
Section: Analysis Of Data Available In September 2015mentioning
confidence: 99%